(untitled) (American Journal of Business Management, Economics and Banking, 2024)
The article examines the theoretical foundations of investment and substantiates the role and necessity of investment in the development of the national economy. The main trends of investments in fixed assets by sources of financing, as well as the reproductive and technological structure of investments in fixed assets in the Republic of Uzbekistan in 2022 are analyzed. In conclusion, scientific conclusions were formulated and practical recommendations for the development of investment activities in the country were developed.